2018
DOI: 10.1111/eff.12442
|View full text |Cite
|
Sign up to set email alerts
|

The effect of physiological and environmental conditions on smolt migration in Atlantic salmon Salmo salar

Abstract: Hydropower development has negatively influenced Atlantic salmon (Salmo salar)populations. Compensatory hatchery-rearing programmes exist, but released fish suffer from high mortality that may be related to the lack of experience from natural environments in hatchery-reared smolts and their large body size and high energetic state. Here, we used acoustic telemetry to test how body size, energetic state, and the environmental conditions of the river affect migration in hatchery-reared smolts.The study was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Nevertheless, Zydlewski et al (2014) The results also suggest an effect of the hydrological conditions on smolt spring migration. Similar observations have been reported in field studies, where a sharp increase in river flow can stimulate smolt migration activity (Aldvén et al, 2015;Antonsson & Gudjonsson, 2002;Hvidsten et al, 1995;Jonsson & Jonsson, 2011;Karppinen et al, 2014;Persson, Kagervall, Leonardsson, Royan, & Alanärä, 2019). In the West River basin, Whalen et al (1999) found variability in the influence of river discharge peaks throughout the migration season; responsivity was highest during the mid-season until the physiological status of smolts declined.…”
Section: Environmental Cues and The Phenology Of Smolt Migrationsupporting
confidence: 76%
See 1 more Smart Citation
“…Nevertheless, Zydlewski et al (2014) The results also suggest an effect of the hydrological conditions on smolt spring migration. Similar observations have been reported in field studies, where a sharp increase in river flow can stimulate smolt migration activity (Aldvén et al, 2015;Antonsson & Gudjonsson, 2002;Hvidsten et al, 1995;Jonsson & Jonsson, 2011;Karppinen et al, 2014;Persson, Kagervall, Leonardsson, Royan, & Alanärä, 2019). In the West River basin, Whalen et al (1999) found variability in the influence of river discharge peaks throughout the migration season; responsivity was highest during the mid-season until the physiological status of smolts declined.…”
Section: Environmental Cues and The Phenology Of Smolt Migrationsupporting
confidence: 76%
“…Thus, the discharge peaks are not indispensable for initiating fish migration, but they can promote massive downstream movements during increased river flow. Moving in a group can provide protection against predation (Berdahl, Westley, & Quinn, 2017) and migration during high flow is energetically beneficial (Persson et al, 2019), as also proposed for silver eels Anguilla anguilla (Barry et al, 2016). Nevertheless, smolt activity was not affected by discharge peaks before the spring equinox, suggesting that the sensitivity to hydrological change occurred only after the photoperiod cue had been received.…”
Section: Environmental Cues and The Phenology Of Smolt Migrationmentioning
confidence: 70%
“…We show here that migration timing in these populations seems to be primarily influenced by the timing of river spring floods, though temperature seems more important as the season progresses. The importance of water discharge and temperature in triggering migration has been observed many times elsewhere 3 , 22 , 24 – 26 , 49 , 50 . Here, the degree to which river conditions control the phenology of migration timing is the likely cause of the observed synchronization among rivers with similar hydrological properties.…”
Section: Discussionmentioning
confidence: 80%
“…The statistical analyses revealed that larger sized smolts were more likely to successfully move down through the study area. Recent literature reports both cases where estimated survival is positively associated with length (Chaput et al, 2019; Davidsen et al., 2009; Flávio et al., 2019; Jepsen, Aarestrup, Økland, & Rasmussen, 1998), negatively associated with length (del Villar‐Guerra, Larsen, Baktoft, Koed, & Aarestrup, 2019) and where no effect of smolt length was detected (Dempson et al., 2011; Persson, Kagervall, Leonardsson, Royan, & Alanärä, 2019; both of which tagged larger smolts on average), seemingly indicating that the impact of size on survival may be site‐specific (Gregory, Armstrong, & Britton, 2018). Importantly, while it is not possible to entirely rule out tagging effects on survival, this difference in survival rates between fish lengths is expected to reflect a true difference in fitness, as Newton et al.…”
Section: Discussionmentioning
confidence: 99%